Towards spike-based speech processing: A biologically plausible approach to simple acoustic classification - Uysal, Ismail; Sathyendra, Harsha; Harris, John G. (Zielona Góra: Uniwersytet Zielonogórski)
Shortcomings of automatic speech recognition (ASR) applications are becoming more evident as they are more widely used in real life. The inherent non-stationarity associated with the timing of speech signals as well as the dynamical changes in the environment make the ensuing analysis and recognition extremely difficult.
Keywords: spike coding; synchrony coding; phase locking; speech perception; psychoacoustics; speech recognition